Hypertension in Pregnancy - Adnan Al-Ward, Mais; Hameed Abdulridha, Ruaa; Adel Hussein, Marwa; Jasim Sodani, Ibtisam; Ridha Jaafar, May; Khalid Ibrahim Al-Sammarrie, Hala; A. Jawad, Asmaa; Emad Neamah, Shahad; Hussen Safir, Nadhum (Al-Nahrain Journal of Science, 2024)
Hypertensive disorders during pregnancy are an important global health problem and a leading cause of maternal death in underdeveloped countries. While therapeutic choices have remained mostly unchanged in recent years, there have been notable advancements in understanding the etiology of preeclampsia. on an accurate diagnosis, particularly by the emergency physician. The appropriate care for these patients relies significantly harm to the cardiovascular and other organ systems. This study has been providing the most recent information on the many hypertension diseases that occur during pregnancy and the available treatment choices.